Inari Sami folklore : stories from Aanaar - Koskimies, Aukusti Valdemar, 1856-1929; Itkonen, T. I. (Toivo Immanuel), 1891-1968 (The University of Wisconsin Press, 2019)
This anthology of folk tales, legends, joik-songs, proverbs, riddles, and omens represent the most comprehensive collection of Sámi oral tradition available in English to date. Collected in 1886 by A.V. Koskimies in the small arctic village of Aanaar (Inari), Finland, and later augmented by Toivo Itkonen and Lea Laitinen, it includes more than 150 stories and songs, and hundreds of proverbs, omens, and riddles, from nearly two dozen storytellers. It paints a picture of late nineteenth-century life in Aanaar, showing important changes occurring within the community, the hopes and fears of local people, and the complex web of social relations that existed both inside and outside the community.